Where does subcutaneous lymph from the chest wall flow into after mastectomy?. Issue 11 (November 2021) - Akita, Shinsuke; Yamaji, Yoshihisa; Tokumoto, Hideki; Tezuka, Takafumi; Ogata, Hideyuki; Kosaka, Kentaro; Kanai, Masahiko; Kuriyama, Motone; Mitsukawa, Nobuyuki
Summary: Background: Changes of the lymph flow from the chest wall after mastectomy and sentinel lymph node biopsy (SLNB) or axillary lymph node dissection (Ax) has yet to be understood. This study aimed to investigate the effect of axillary surgery on lymphatic flow from the chest wall in patients who have undergone mastectomy, including those have undergone breast reconstruction and vascularized lymph node transfer (VLNT). Methods: Following mastectomy in 100 breasts, the directions of lymph flow from the chest wall was compared between the SLNB omission, SLNB, Ax, and Ax followed by VLNT groups using indocyanine green (ICG) lymphography in cross-sectional study. Lymph flow on the deep epigastric artery perforator (DIEP) flap was also investigated. Results: Lymph flow directing to the ipsilateral axilla was observed more frequently after SLNB than Ax (48% vs. 12.5%; p = 0.005); however, no significant difference was observed in the frequency of contralateral axillary route adoption between them (8% vs. 15%; p = 0.65). In the VLNT group, lymph flow to the ipsilateral axilla was not observed at a significantly higher frequency than in the Ax group (12.5% vs. 12.5%, p = 1.00). On the transferred DIEP flap, the lymph flowed anterograde or retrograde parallel to the anatomic course of the lymphatic vessels. Conclusion: To visualize the direction of lymph flow of the chest following mastectomy, ICG lymphography may be useful to discern the direction in which malignant neoplasms, including lymphoma, are transported and to plan for lymph flow restoration.